The Effect of Plasma Osmolality on Prognosis in Non-Massive Pulmonary Embolism - Eraslan, Berrin Zinnet; Kodalak-Cengiz, Sümeyye; İçmeli, Özlem Saniye; Kiral, Nesrin; Şener-Cömert, Sevda (Cerrahpaşa Medical Journal, 2025)
Objective: Plasma osmolality provides insight into fluid and electrolyte balance and can serve as a prognostic marker in critically ill patients. There is limited research on the relationship between plasma osmolality and mortality in pulmonary embolism (PE). The potential role of plasma osmolality in predicting mortality in PE patients is examined in this study. Methods: A retrospective analysis was conducted on patients admitted to the chest diseases ward with acute PE. Data on demographics, comorbidities, clinical and laboratory results, in-hospital mortality, and 30-day mortality were collected. Plasma osmolality was calculated using sodium, plasma glucose, and blood urea nitrogen (BUN) levels at admission. Patients were categorized into hyposmolality, normosmolality, and hyperosmolality groups. Results: The study included 226 patients (100 males, 44.2%), aged 23-90 years. In-hospital mortality occurred in 13 patients (5.8%). The mortality rate was significantly higher in patients with a simplified Pulmonary Embolism Severity Index score ≥1 (P = .031). In addition, lower albumin levels (P = .008) and higher BUN (P = .007) and urea levels (P = .005) were significantly associated with in-hospital mortality. No significant differences in D-dimer, creatinine, glucose, sodium, and osmolality levels were observed between patients who were discharged and those who experienced in-hospital mortality. Mortality rates within 30 days did not significantly differ across osmolality groups (P > .05). Conclusion: This study did not find a significant correlation between plasma osmolality and short-term mortality in patients with acute PE. Cite this article as: Eraslan BZ, Kodalak-Cengiz S, İçmeli ÖS, Kiral N, Şener-Cömert S. The effect of plasma osmolality on prognosis in non-massive pulmonary embolism. Cerrahpaşa Med J. 2025; 49, 0050, doi: 10.5152/cjm.2025.24050.